The Practice of Silence for Achieving Spiritual Perfection - Hendi Hendi (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2023)
The most important things about this paper are that Christians find perfection in the spiritual world, by being saved immediately and for all time through Christ. The exercise of silence and hesychia is the way to achieve perfection, and it can be applied to us nowadays. The goal of this article is to discover Apophthegmata Patrum in terms of the answers given in the sayings of the Desert Fathers. Silence and hesychia are crucial elements of monastic life, as are the elements of spiritual perfection such as the purification of sins, or logismoi, the renunciation of the world, or repose, listening to and loving God, and discovering the Kingdom of God within the heart. The practice of silence for us living nowadays is to build our spiritual cell in the silence and repose of this busy world. The cell is the first step toward silence, followed by the hesychia.